Study on leadership competencies among bachelor in information studies students in UiTM Kedah / Rosni Rosli - Rosli, Rosni (Faculty of Information Management, 2010)
This assignment was done to fulfill the requirement for the subject IML 551 or Research Methodology. The research entitled is “Study on Leadership Competency among BIS Student part 3, 4 and 5. Study on Leadership is an elusive concept or field. Actually leadership is one of the processes resulting from complex social interactions between a leader and followers within a specific context. In education concept, leadership is one of the important elements in produce a good student for work field in the future. Therefore, this research will conduct the student behaviors in order to know they have all the personal traits on leadership aspect. The respondents of this study generally among student in Bachelor Information Studies Part 3, 4 and 5 at University Technology Mara, Kedah. The objectives of this study are to investigate the factors influence people to be a good leader, to study the student's behavior on leadership fields and to reveal the competency of leadership among BIS student. In this study, there are include one dependent variable and three independent variables. The dependent variable is the competency personal traits of leadership among BIS students at UiTM Kedah. The independent variables indicate that competency of leader such as skill, knowledge and attitudes